2014
DOI: 10.1128/jvi.03032-13
|View full text |Cite
|
Sign up to set email alerts
|

Two Membrane-Associated Regions within the Nodamura Virus RNA-Dependent RNA Polymerase Are Critical for both Mitochondrial Localization and RNA Replication

Abstract: Viruses with positive-strand RNA genomes amplify their genomes in replication complexes associated with cellular membranes. Little is known about the mechanism of replication complex formation in cells infected with Nodamura virus. This virus is unique in its ability to lethally infect both mammals and insects. In mice and in larvae of the greater wax moth (Galleria mellonella), Nodamura virus-infected muscle cells exhibit mitochondrial aggregation and membrane rearrangement, leading to disorganization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Expression of the polymerase of Nodamura virus, also a nodavirus, induced mitochondria to cluster into distinct cytoplasmic networks. It was shown that nodavirus RNA synthesis localises to these polymerase-induced mitochondrial networks, establishing the polymerase as a key protein for the assembly of membrane-anchored replication complexes (Gant et al, 2014). Our unexpected finding of a redistribution of Golgi membranes in cells expressing the RHDV polymerase, or the entire virus polyprotein, strongly indicates that RHDV employs the polymerase to utilise modified membranes of the secretory pathway for its replication.…”
Section: Redistribution Of Golgi Membranes In Cells Expressing the VImentioning
confidence: 81%
“…Expression of the polymerase of Nodamura virus, also a nodavirus, induced mitochondria to cluster into distinct cytoplasmic networks. It was shown that nodavirus RNA synthesis localises to these polymerase-induced mitochondrial networks, establishing the polymerase as a key protein for the assembly of membrane-anchored replication complexes (Gant et al, 2014). Our unexpected finding of a redistribution of Golgi membranes in cells expressing the RHDV polymerase, or the entire virus polyprotein, strongly indicates that RHDV employs the polymerase to utilise modified membranes of the secretory pathway for its replication.…”
Section: Redistribution Of Golgi Membranes In Cells Expressing the VImentioning
confidence: 81%
“…7C, in which green (CTXB) and red (BLT1) signals are assigned to the x and y axes, respectively. Each pixel is represented as a dot, and pixels with well co-localized signals appear as a scattered diagonal line [41, 42]. The average Manders’ overlap coefficients for MCF-7 cells (0.41 ± 0.013) and MDA MB 231 cells (0.90 ± 0.045) suggest strong colocalization between CTXB and BLT1 along the cell membrane of MDA MB 231.…”
Section: Resultsmentioning
confidence: 99%
“…Although polymerase-dependent membrane rearrangements were described for members of Nodaviridae family, such as Flock house virus and Nodamura virus , it should be noted that the RdRps of these viruses are twice as large as their RHDV and RCV counterparts and that they carry distinct functional domains in addition to the core polymerase structure present in all RdRps [26, 27]. Rabbit calicivirus RdRps, on the other hand do not have any obvious domains or motifs that could be easily linked to the observed Golgi membrane rearrangements.…”
Section: Discussionmentioning
confidence: 99%